Educational Venue from Design to Implementation Process; A Project by Faculty of Fine Arts, Selçuk University - Mine Sungur; İbrahim Bakır (Turkish Journal of Agriculture: Food Science and Technology)
Throughout history, there has been a reciprocal relationship between humans and space. Even though there are numerous spaces covered by this ongoing relationship process, it has integrated and gained value with educational venues. Mainly because they closely monitor social, cultural, technological, and economic developments and pass on knowledge to future generations, educational spaces play a crucial role in the development of individuals as well as society. It is feasible to conclude from research on educational spaces that the physical environment has a major positive or negative impact on education. To solve the issue that the current Faculty of Fine Arts at Selçuk University could not sufficiently respond to user needs physically, it was decided to construct a new Faculty of Fine Arts building. The primary goal of the study is to design the building using user-oriented techniques that promote social interaction and showcase artistic identity throughout the design phase. A qualitative research approach, based on inspection and observations, was used in the study to gather data, documents, and reports on the topic and to ensure that the architectural programming stages advanced correctly and received ongoing feedback. Studies have confirmed the results, which show that artistic education in structures that provide users with distinct experiences is different from that provided in faculty buildings with a type plan scheme. The process, which involves collaboration between stakeholders from various disciplines and necessitates coordination, is also maintained in a coordinated fashion as a consequence of the study. Because of this, it is believed that buildings with comparable features can offer direction by offering a set of data that may also be reliable for design procedures that are prearranged.